CEUNES: Centro Universitário Norte do Espírito Santo - Andrade Teixeira, Saffira; dos Santos, Joana Carla; Costa Velten, Ana Paula; da Silva Santos Morais, Lavínia; Mascarello, Keila Cristina; Vital de Oliveira, Maria Fernanda; Bubach, Susana; Soprani dos Santos, Andreia; da Silva Vieira, Jéssica Ariel; Batista do Nascimento, Lorrayne; Zequineli Constantino, Deyse Emilly; Pereira Coelho, Marta; et al. (Guará Journal, 2023)
Resumos dos Projetos do Centro Universitário Norte do Espírito Santo